Pengaruh Bias Perilaku Investor Terhadap Keputusan Investasi Di Pasar Saham - Yopi Adhimas Fitra (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2023)
The goal of this study was to analyze and collect data on the variables that affect a person's ability to make informed investing decisions. 158 respondents made up the study's sample population. The information utilized this research were primary data collected using survey methods, and the sample was gathered through the distribution of research questionnaires. The The findings of this study demonstrate that herding behavior positively affects investment choices, Heuristic Behavior has no effect on Investment Decisions, Disposition Effect has a positive effect on Investment Decisions, and Attitudes on Risk have a negative and significant effect on Investment Decisions. And recommendations for more study are anticipated to be a reference in making decisions and adjusting the variables used with each other's psychology before making investment making choices so they can reduce risk and increase the revenue obtained and also before making decisions for novice investors are expected to try to learn the concept invest or ask friends or individuals who have experience in investing before making a decision because it is important to reduce the risk of loss and encourage success in investing in securities, especially stocks.